A study on the employees perception towards organizational politics: Case study at Selangor Islamic Religious Council (MAIS), Shah Alam, Selangor / Muhammad Adib Ibrahim Fekri and Abdul Hadi Hassan - Ibrahim Fekri, Muhammad Adib; Hassan, Abdul Hadi (Faculty of Administrative Science and Policy Studies, 2013)
In Malaysia nowadays, no matter the employees work in high rank or low rank, the organizational politics still occurs. Work in large organization, small companies, even though work in tavern though, there is political work among us all. Political work will determine the power, influence and even determine whether the work flow running smoothly. In office politics, this work has many other factors, such as the average age of a colleague, nationality, race, economic background and so forth. The objectives of this study are to determine the most influential factor that contributes to organizational politics at Selangor Islamic Religious Council (MAIS). Stratified and simple random samplings have conducted over 132 respondents at Selangor Islamic Religious Council (MAIS).